CREB serine 133 is necessary for spatial cognitive flexibility and long-term potentiation. (15th November 2022) - Morè, Lorenzo; Privitera, Lucia; Perrett, Philippa; Cooper, Daniel D.; Bonnello, Manuel Van Gijsel; Arthur, J. Simon C.; Frenguelli, Bruno G.
Abstract: The transcription factor cAMP response element-binding protein (CREB) is widely regarded as orchestrating the genomic response that underpins a range of physiological functions in the central nervous system, including learning and memory. Of the means by which CREB can be regulated, emphasis has been placed on the phosphorylation of a key serine residue, S133, in the CREB protein, which is required for CREB-mediated transcriptional activation in response to a variety of activity-dependent stimuli. Understanding the role of CREB S133 has been complicated by molecular genetic techniques relying on over-expression of either dominant negative or activating transgenes that may distort the physiological role of endogenous CREB. A more elegant recent approach targeting S133 in the endogenous CREB gene has yielded a mouse with constitutive replacement of this residue with alanine (S133A), but has generated results (no behavioural phenotype and no effect on gene transcription) at odds with contemporary views as to the role of CREB S133, and which may reflect compensatory changes associated with the constitutive mutation. To avoid this potential complication, we generated a post-natal and forebrain-specific CREB S133A mutant in which the expression of the mutation was under the control of CaMKIIα promoter. Using male and female mice we show that CREB S133 is necessary for spatial cognitive flexibility, the regulation of basal synaptic transmission, and for the expression of long-term potentiation (LTP) in hippocampal area CA1. These data point to the importance of CREB S133 in neuronal function, synaptic plasticity and cognition in the mammalian brain. Highlights: The transcription factor CREB is required for learning and memory. The specific role of phosphorylation of CREB serine 133 is unclear. We have made a conditional forebrain specific CREB S133A mutant. The CREB S133A mutant displays deficits in cognitive flexibility and LTP. CREB S133 is therefore key to CREB's role in plasticity and cognition.